Lógicas institucionais e as respostas estratégicas diante da prática de acreditação hospitalar nos hospitais do Estado do Rio de Janeiro - Silva, Tiago Martins Ramos da (2016)
The objective of this study is to analyze how the institutional logics determine the strategic responses of the organizations on the adoption of hospital accreditation practice in hospitals in Rio de Janeiro. To achieve this objective, we designed an analytical framework with extracted analysis of categories of studies such as from Oliver (1991), Thornton and Ocasio (2012), Meyer and Rowan (1977), Pache and Santos (2010) and Scott (2008). The study is relevant to the hospital field because it analyses the practice of an important quality management method in public and private hospitals in the State of Rio de Janeiro. The study evaluated four hospitals in Rio de Janeiro with the hospital accreditation certificate: Brazilian Accreditation Consortium - CBA or the National Accreditation Organization - ONA. The research was made through interviews in depth and questionnaires applied to appraisers, managers and employees of each organization. After analyzing the results, the research concludes that institutional logics have a direct impact on strategic responses of the organizations, as well as different dominant logic may cause different strategic responses of the organizations. The study theoretically contributes to the field of organizational studies as it emphasizes the importance of institutional logics as a very important element in assessing the strategic responses to the adoption of organizational practices.